Consumer value creation through WhatsApp use: A qualitative multimethod approach in a Latin American scenario - Cruz-Cárdenas, Jorge (2019)
The purpose of this paper is to understand in-depth how consumers create value in their lives using WhatsApp, the leading mobile instant messaging (MIM) application. Design/methodology/approach: The study adopts the perspective of customer-dominant logic (CDL) and uses a qualitative multimethod design involving 3 focus groups and 25 subsequent in-depth interviews. The research setting was Ecuador, a Latin American country. Findings: Analysis and interpretation of the participants’ stories made it possible to identify and understand the creation of four types of value: maintaining and strengthening relationships; improving role performance; emotional support; and entertainment and fun. In addition, the present study proposes a conceptual model of consumer value creation as it applies to MIM. Practical implications: Understanding the way consumers create value in their lives using MIM is important not only for organizations that offer MIM applications, but also for those companies that develop other applications for mobile phones or for those who wish to use MIM as an electronic word-of-mouth vehicle. Originality/value: The current study is one of the first to address the topic of consumer behavior in the use of technologies from the perspective of CDL; this perspective enables an integrated qualitative vision of value creation in which the consumer is the protagonist.